The Transition to Higher Education: A Comparative Study of US and Irish Students - Abbott, Abigail (Trinity College (Dublin, Ireland). School of Education, 2021)
Current research on the mental health and wellbeing of undergraduate students indicates that many students are struggling to adjust to the social, emotional, and academic demands of undergraduate education. The key challenges students face typically fall into two categories: academic challenges (e.g. academic writing skills; study skills) and soft skill challenges (e.g. time-management; managing finances). This study seeks to better understand specific challenges students face and how schools can better prepare students for the transition to higher education. The study draws upon quantitative and qualitative data obtained from a questionnaire that measures the challenges students face in higher education, academic and non-academic skills taught in secondary school, and students perceptions of how secondary schools can better prepare students for the transition to higher education. The study indicates that the main challenges the participants face include time-management and stress-management. This is found for both US and Irish students. Additionally, the participants suggest that secondary schools can better prepare students for the transition to college by educating students on practical life skills/soft skills, promoting student independence, and informing students about academic expectations in higher education. A difference that emerged between the US and Irish participants was that more Irish participants suggested that secondary schools could better prepare students for the transition to college by promoting student independence. A second key difference that emerged between the cohorts was that the majority of the US students referred to academic skills when describing the most effective way their high school prepared them for college. Alternatively, the Irish students referred to both academic skills and soft skills when explaining how their secondary schools prepared them for college.
Keywords: Positive Behaviour Management; Education